The Effect of Financial Literacy, Performance Expectancy, Effort Expectancy, and Money Saving to Use Decision Financial Technology in the Millennial Generation in North Bekasi - Dody Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was used to The Effect of Financial Literacy, Performance Expectancy, Effort Expectancy, and Money Saving To Use Decision Financial Technology In The Millennial Generation in North Bekasi. This research is quantitative research where the object used is an employee in a use decision financial technology millennial generation in north Bekasi. This research was conducted using a non-probability sampling technique with a purposive sampling method. The number of samples used in this study was 152 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 4.0. The results of this study provide an explanation that the financial literacy variable affects the use of decision financial technology, performance expectancy affects the use of decision financial technology, effort expectancy affects the use of decision financial technology, and money saving affects the use of decision financial technology.